Standardization of Pres Owing Treatments for Different Seabuckthorn Species in Cold Deserts of Himachal Pradesh - Sankhyan, H. P.; Sehgal, R. N.; Bhrot, N. P. (Indian Forester, 2005)
Seabuckthorn is a wonderful plant for the afforestation and ecological rejuvenation of the cold desert areas of Himalayas where plantations of poplars, willows and robinia have not given very encouraging results. It has the potential to economically transform these harsh and marginal areas plagued by low productivity. Keeping in view, almost complete lack of information in India on regeneration through seed the present investigation was carried out to standardize various presowing treatments in two species of Sea buckthorn in the cold desert of Himachal Pradesh. Different presowing treatments were hot water (80DC for 10 minutes), conc. H2S04 (20 minutes), cold water for 2,4 and 6 days, cow dung heap for 2 days and control. In case of Hippophae rhamnoides, the best presowing treatment was found to be cold water soaking for 6 days which resulted in the highest germination per cent (93.33), per cent survival (73.33), growth index (69.78) and SVI (8502.36). However, for H. salicifolia soaking treatment in hot water at 80DC for 10 minutes was found to be the best and resulted in the highest germination per cent (76.66), per cent survival (60.00), shoot length (45.6 cm), root length (70.9 cm), growth index (39.90) and SVI (8930.89) and ranked first.